A method to decompose spectral changes in Synechocystis PCC 6803 during light-induced state transitions - Acuña, Alonso M; Kaňa, Radek; Gwizdala, Michal; Snellenburg, Joris J; van Alphen, Pascal; van Oort, Bart; Kirilovsky, Diana; van Grondelle, Rienk; van Stokkum, Ivo H M (Photosynthesis research, 2016)
Cyanobacteria have developed responses to maintain the balance between the energy absorbed and the energy used in different pigment-protein complexes. One of the relatively rapid (a few minutes) responses is activated when the cells are exposed to high light intensities. This mechanism thermally dissipates excitation energy at the level of the phycobilisome (PB) antenna before it reaches the reaction center. When exposed to low intensities of light that modify the redox state of the plastoquinone pool, the so-called state transitions redistribute energy between photosystem I and II. Experimental techniques to investigate the underlying mechanisms of these responses, such as pulse-amplitude modulated fluorometry, are based on spectrally integrated signals. Previously, a spectrally resolved fluorometry method has been introduced to preserve spectral information. The analysis method introduced in this work allows to interpret SRF data in terms of species-associated spectra of open/closed reaction centers (RCs), (un)quenched PB and state 1 versus state 2. Thus, spectral differences in the time-dependent fluorescence signature of photosynthetic organisms under varying light conditions can be traced and assigned to functional emitting species leading to a number of interpretations of their molecular origins. In particular, we present evidence that state 1 and state 2 correspond to different states of the PB-PSII-PSI megacomplex.
Keywords: Fluorescence; světlo; Synechocystis; Photosystem II Protein Complex; Spectrometry, Fluorescence; Light; Spectrally resolved fluorometry; Photosystem I Protein Complex; fluorescenční spektrometrie; Cyanobacteria; fotosystém I (proteinový komplex); fluorescence; fotosystém II (proteinový komplex); Singular value decomposition; Time-resolved spectroscopy